A history of homosexuality in Europe : Berlin, London, Paris, 1919-1939. - Tamagne, Florence, 1970- (Algora, 2004)
Just crawling out from under the Victorian blanket, Europe was devastated by a gruesome war that consumed the flower of its youth. Tamagnedissects the strands of euphoria, rebellion, exploration, nostalgia and yearning, and the bonds forged at school and on the battlefront, in a scholarly treatise charting the early days of the homosexual and lesbian scene. The period between the two world wars was crucial in the history of homosexuality in Europe. It was then that homosexuality first came out into the light of day. Berlin became the capital of the new culture, and the center of a political movement seeking rights and protections for what we now call gaysand lesbians. In England, the confruntation was brisk to undermine the structures and strictures of Victorianism; whereas in France (which was moretolerant, over all), homosexuality remained more subtle and nonmilitant.